Effects of Glutamate on Growth Performance, Gut Digestion and Antioxidant Capacity in Juvenile Little Yellow Croaker - Ruining Liu; Yu Zhang; Xiao Liang; Bao Lou; Junquan Zhu (Fishes, 2025)
This study is to explore the alleviating effects of glutamate on intestinal damage in cultured little yellow croaker. A total of 900 juvenile fish at a weight of 30.68 ± 0.12 g were randomly separated into six groups with three replicates each, and were fed a basic diet (protein at 44.42% and lipid at 12.48%) with additional glutamate at 0.00%, 0.40%, 0.80%, 1.2%, 1.60%, and 2.00%. Each replica group consisted of 50 fish in a breeding barrel (radius 1.0 m, height 1.5 m), and the experiment lasted for 54 days. The results showed that supplementation with 0.4–1.2% glutamate significantly improved the survival rate, which increased from 75.56% to 91.11%, reduced the feed conversion rate from 1.75 to 1.57, and increased the protein efficiency ratio from 1.55 to 1.85 (p

Global assessment of radiative cooling and low-emissivity coatings for energy efficiency in buildings across all climate zones - Jiashuo Wang; Zekai Li; Tongyu Zhou; Wu Deng; Runqi Liang; Isaac Yu-Fat Lun; Yilin Li; Ruining Bao (Energy and Buildings, 2024)